Managers' Decisions About Informal Accommodation Requests by Employees With and Without Disabilities - Bonaccio, Silvia; Connelly, Catherine E.; McLarnon, Matthew J. W.; Gellatly, Ian R. (Human Resource Management, 2026)
ABSTRACT Although formal accommodations are required by law across many jurisdictions, many employees seek informal adjustments to their work conditions. These individualized work arrangements are not rooted in legal compliance but are instead provided at managers' discretion. Employees without disabilities routinely ask for changes to their work conditions (e.g., flexible work arrangements), and these changes often mirror those requested by employees with disabilities. Using Social Exchange Theory as our conceptual lens, we examined the critical role of managers' decision‐making on informal accommodation requests through three policy‐capturing studies. As hypothesized, managers were more likely to grant informal accommodations to employees with longer tenure, stronger task performance, and more citizenship behaviors. Moreover, tenure consistently had the strongest influence on accommodation intentions. Managers were also more likely to grant informal accommodations for disability reasons than for family‐related reasons, contrary to our expectations. Our research offers novel insights into how managers view informal accommodation requests from employees with and without disabilities. This study provides crucial theoretical contributions to the human resource management literature and informs practical considerations on issues faced by managers and organizations.